A Review of the Use of Particle Accelerators as a Potential Wastewater Treatment Application: What We Know and What We Need to Know - Bloetscher, Frederick; Meeroff, Daniel E.; Shaha, Bishow; Cooper, Charles (European Journal of Applied Sciences, 2022)
A workshop entitled, “Workshop on Application of Electron Beam Technology on Wastewater and Biosolids Treatment,” was held in May 2018 at the Fermi Lab outside Chicago, IL to discuss the use of particle accelerator technology for wastewater treatment and biosolids management, inform wastewater treatment professionals about particle accelerator technology and application opportunities in the treatment of wastewater, and to provide feedback to the sponsor NSF on suggested future funding needs to encourage accelerator installation. Conclusions were that there was a need to develop demonstration projects, adding to those done in Boston in the late 1970s, Miami in the 1980s to identify costs and limitations for implementation. Education of the public as to how accelerators operate, costs of operation and the benefits derived was also an identified need given the lack of actual large-scale implementation for water treatment in the United States and limited data overseas. The cost to develop and install accelerators suggests funding from NSF and the Department of Energy Stewardship program could help utilities develop more succinct treatment protocols.